Of Floods and Droughts : The Economic and Financial Crisis of 2008 - Islam, Roumeen; Nallari, Raj (2012)
This paper provides an overview of the period prior to the recent global crisis, and the policies that were adopted around the world in response to the crisis. It highlights a number of key issues regarding economic and financial policies that governments have faced both globally and nationally. These are related to the management of boom and bust episodes that deserve more attention in policy circles in the future.